Gestão processual proporcional: técnicas básicas de gestão estratégica como meio de efetivação do princípio da eficiência - Daniel Calazans Palomino Teixeira (2021)
The essay approaches strategic procedural management in its proportional perspective, analyzing the application of basic management techniques to make Judiciary Branch more efficient. After aligning premises about the subject (including associated fundamental procedural rules) and exposing some of the main current techniques of strategic management (aiming to make them more accessible to the legal community), the essay focuses the perspectives of strategic procedural management (flexible, collaborative, and proportional) to comprehend the results of proportional procedural management in Brazil. The essay concludes that it’s important that the Judiciary Branch has a strategic and proportional procedural management to make judicial process efficient and consequently fair (prompt, effective and adequate).